Disaster Preparedness among Households in the Municipality of Pura, Tarlac: An Analysis - Caoleng, Edwin T.; Fermin, Roswald G. (Journal of Ecohumanism, 2024)
This research endeavors to evaluate the level of disaster preparedness among households in the Municipality of Pura, Tarlac, employing a quantitative descriptive research approach. A survey questionnaire was utilized to gather data from 112 household respondents, selected through random sampling across barangays most vulnerable to disasters. Data analysis, facilitated by SPSS analytical statistics software, focused on identifying trends and correlations between disaster preparedness levels and encountered challenges. The findings reveal both strengths and challenges in disaster preparedness. While emergency plans, risk awareness, and response capacity demonstrate commendable efficacy, deficiencies in emergency supplies, community engagement, and infrastructure persist. Correlation analysis underscores the positive relationship between proactive measures and mitigation of challenges, emphasizing the importance of investing in comprehensive disaster management strategies. Recommendations are proposed based on the research findings. Strengthening emergency supplies and resources through equitable distribution mechanisms and community collaboration is advised. Fostering greater community engagement and collaboration, enhancing emergency plans, and improving response and recovery capacity are also recommended. These measures, encompassing workshops, collaboration initiatives, and resource provisions, aim to empower households with the necessary knowledge and resources for effective disaster preparedness, response, and recovery. Implementation of these recommendations is crucial for enhancing disaster resilience and readiness in the Municipality of Pura, Tarlac. By addressing identified challenges and bolstering proactive measures, the community can better safeguard its residents and infrastructure against future disasters, ensuring their safety and well-being.